After the Anthropocene: Time and Mobility - Heikkurinen, Pasi; Ruuska, Toni; Valtonen, Anu; Rantala, Outi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book discusses the geological time that will follow the human-dominated epoch and ways to move there. In addition to an editorial, a total of five articles are published in this volume. The articles engage with a variety of social science disciplines-ranging from economics and sociology to philosophy and political science-and connect to natural science's insights into the Anthropocene. The volume calls for going beyond anthropocentrism in sustainability theory and practice in order to exit the Anthropocene with applications and insights in the contexts of politics, energy, tourism, food and management. We hope that you will find this book interesting and helpful in contributing to sustainable change.